Catering Group Piano Curriculum for the Music Educators of the Next Generation - Chee Hyeon Choi Dr. (Journal of the Association for Technology in Music Instruction, 2020)
Advances in consumer technology have drastically changed the ways students access and appreciate music. As a result, teaching materials in group piano curriculum have become quickly outdated. Students no longer recognize folk tunes that have been sung or used for harmonization exercises; they prefer to listen and play music on their playlist stored in their mobile devices. Although pedagogical principles and objectives should persist over time, teaching methodologies and materials should continuously be updated to increase students’ engagement in learning. The newer generation of students favor classes that are more practical, satisfy their personal interests, and meet their degree program expectations. Since education majors require keyboard proficiency, group piano programs play a critical role in their learning. Collegiate group piano classes can be a steppingstone for cultivating a wider range of audiences by utilizing instructional technology. Empowering these students with innovative keyboard skill curricula ultimately delivers positive results to the future generation. Integration of technology and innovative class projects help create engaging class sessions that actively draw learners’ participation, enable deeper learning, and gain strategies to apply in their future teaching career.
Keywords: technology integration; innovative group piano instruction; technology assisted learning